KAPASITAS LEMBAGA BADAN PERMUSYAWARATAN DESA BULUH CINA KECAMATAN SIAK HULU KABUPATEN KAMPAR DALAM MEMBUAT PERATURAN DESA TAHUN 2010 - ', Adlin; Amin, Raja Muhammad; ', Isril (Universitas Riau, 2011)
Badan Pemusyawaratan Desa (BPD) are an institutionalism was held the governance in village that mustbe function as a legislation in village and so BPD gives some authority to discuss about the rules ofvillage with head of village. BPD in Buluh Cina on 2010 doesnt have capacity for make a rules of village tokeep the norm of society or rules of village to take some money to increase income a village in orderBuluh Cina Village are a tourisme village with a natural potentionand his culture. This research describesa factors that cause the weakness of BPD Buluh Cina to make a rules a village. Kualitative descriptivemethods with sampling puprossive technic are used with gets data from depth interview with informanuntill researcher get the valid information. This research show that model?s of recruitment BPD wasdomination from elite of village. Societies choice the candidate dont have a popularities and so manycandidates dont know and dont have a science to be a BPD. Supra government in a village also never doa workshop for BPD and minim of salary also be a reason for BPD in Buluh Cina Village to do evectivelly.Keywords: Recruitmen, Capacity of candidate, workshop, salary and institutionalism capacity.